The real-world efficacy of botulinum toxin type a (botox®) for the prophylaxis of headaches in adult patients with chronic migraine in australian clinical practice: a retrospective chart review. Issue 5 (8th May 2017) - Stark, Catherine; Stark, Richard; Limberg, Nicole; Andrews, Colin; Rodrigues, Julian; Cordato, Dennis; Schwartz, Raymond; Michelle, Frost J; Jonathan, Tan
Abstract : Objectives: To determine the real world efficacy of BOTOX for the prophylaxis of headaches in adult patients with chronic migraine (CM) treated through the Pharmaceutical Benefits Scheme (PBS). Methods: The medical charts of CM patients treated consecutively by seven clinicians in 5 Australian states/territories were reviewed. Patients who received BOTOX treatment for CM following PBS listing March 2014 and had headache data recorded after the 2nd treatment cycle were included. The primary response measure was the PBS continuation criterion: a≥50% reduction in the number of headache days per month (HDPM) following two BOTOX treatment cycles. Other data collected included demographics, clinical characteristics, headache frequency and medication use. Results: Data for 211 patients (89% females) were included in the analysis. Mean age was 45 years old; mean time since diagnosis with CM was 13.5 years and patients had failed a mean of four oral headache prophylactics; most commonly amitriptyline, topiramate, propranolol and pizotifen. At baseline the majority used acute migraine medicines, mostly simple analgesics and triptans but also opioids and 61% had a management plan in place for medication overuse headache. Following two BOTOX treatment cycles (median dose 155U, mean time of assessment 27 weeks), 74% had obtained a≥50% reduction in HDPM; from 25±5 HDPM (mean±SD) to 11±8 HDPM. Acute medication intake was reduced from 19±8 days to 7±6 days per month and there were reductions in the proportions of patients using opioids (over the counter codeine from 44% to 28%; prescribed opioids from 23% to 13%). Conclusions: In an Australian clinical practice review, almost three-quarters of CM patients obtained a meaningful reduction in headache days following two BOTOX treatments, fulfilling PBS continuation criterion. Additionally, the use of acute migraine medicines, including opioids, was reduced.